Sistem Pendukung Keputusan Guru Beprestasi Berbasis Web di SMA Swasta Yapim Sibiru-Biru - Anita; Daniel Ronald S P; Rico Rumapea; Pirma Maleahki Satya Negara Pasaribu (Jurnal Sains dan Teknologi, 2020)
Teachers are a noble profession because it is in their hands that the future of the nation is determined. Teachers must alsobe able to realize and instill the values contained in various knowledge by giving examples and discipline. Based on observations madeat Yapim SiBiru-Biru Private High School located in Deli Tua District, Deli Serdang Regency, Medan has a pattern where teacherselection is done every day by all teachers, as well as in the recapitulated data still manually by administrative staff. and to be submittedto the principal every month. The system takes a long time and requires a set of office stationery so that over time there will be abuildup of data in the form of sheets of paper that have been absent for years. Therefore, researchers provide a solution to create awebsite-based decision support system for outstanding teachers as a tool in calculating each criterion used by the SAW (SimpleAdditive Weight) method.